Economic nationalism conceptions: theoretic-methodological aspect - Glushko, Tatiana (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2013)
The aim of thе article is to outline the major lines of the theoretical and methodological foundations of the economic nationalism conceptions, as a branch of philosophical and economic thought. The last one was formed in the 19 century in F. List s works, and now is threpresented by the constellation of the thinkers, including the contemporary ones. Deficiency of a theoretical comprehension the economic nationalism in the current socio-philosophic literature encourages us to further actualization of these conceptions and researching its theoretical and methodological features